2012
DOI: 10.12659/msm.883343
|View full text |Cite
|
Sign up to set email alerts
|

A 6-week training program increased muscle antioxidant system in elderly diabetic fatty rats

Abstract: SummaryBackgroundIt is widely accepted that oxidative stress is associated with the physiopathology of type 2 diabetes mellitus. In fact, it has been pointed out as a therapeutic target in T2DM. Fortunately, several papers have reported that long-term training programs improved the antioxidant system in young and adult diabetic rats. Accordingly, this study was designed to assess the influence of a shorter training program in elderly diabetic fatty rats.Material/MethodsStudy subjects were 24 male homozygous Zu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
(21 reference statements)
1
11
0
Order By: Relevance
“…On Day 1, rats exercised in a Morris water tank (150 cm × 60 cm × 45 cm; water temperature 32 ± 1°C) for 10 min. The acclimation period was extended by 10 min every day (except for the DsbE group) until the rats could swim for 30 or 40 min . The duration of the training phase was 6 weeks (total 150 min/week; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…On Day 1, rats exercised in a Morris water tank (150 cm × 60 cm × 45 cm; water temperature 32 ± 1°C) for 10 min. The acclimation period was extended by 10 min every day (except for the DsbE group) until the rats could swim for 30 or 40 min . The duration of the training phase was 6 weeks (total 150 min/week; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The superoxide dismutase family (SODs) is the first line of defence against reactive oxygen species (ROS) [28]. It is known, that changes in SOD activity protect a host against microorganisms [29,30], bacteria [31,32], and parasites [31] and those changes depend on physical activity, diet, and chemical factors [33,34]. A lower level of total SOD activity in Arabian horses may result from the depletion of the antioxidant defence system due to long exposure to oxidative stress caused by vaccination, handling, and commercial usage.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training can improve cardiovascular performance, leading to increased cardiac pumping efficacy and vascular relaxation 16,17 . Studies have shown that in situations of increased oxidative stress, such as hypertension or diabetes, exercise training reduces the damage caused by oxidative stress in the cardiovascular system 16,18 . However, to date, contradictory views exist concerning the role of physical exercise on redox metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Studies have shown that in situations of increased oxidative stress, such as hypertension or diabetes, exercise training reduces the damage caused by oxidative stress in the cardiovascular system. 16,18 However, to date, contradictory views exist concerning the role of physical exercise on redox metabolism. Published data suggest that acute training, exhaust training and over-training should be prooxidant 19,20 whereas moderate and chronic exercise should be antioxidant, increasing the activity of antioxidant enzymes and combating free radical formation of oxidative metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation